Planned cesarean delivery compared to induction of labor in women with class III obesity: a cost-minimization analysis. (1st October 2016) - Subramaniam, Akila; Corvey, Kathryn J.; Kilgore, Meredith L.; Edwards, Rodney K.
Abstract: Objective : To compare the costs between planned cesarean delivery (CD) and induction of labor (IOL) in women with class III obesity. Methods : We conducted a cost-minimization analysis using data from a previous study of women with a BMI ≥40 kg/m 2 delivering term singletons via planned CD or after IOL. Decision trees were built with branches for two "treatments": planned CD and IOL (probabilities derived from parent study). Direct and total costs were obtained for each mother–infant pair. Sensitivity analyses for probability of successful IOL were performed. Results : A total of 661 mother–infant pairs were included – 399 IOLs and 262 planned CDs. Of 399 IOLs, 236 (59%) delivered vaginally and 163 (41%) had a CD. IOL was slightly less costly. For IOL and planned CD, respectively, direct costs were 7416 versus 7474, and total costs were 11 545 versus 11 665. Sensitivity analyses indicated that IOL was the least costly strategy if the probability of vaginal delivery after IOL was >57% (0.575 for direct costs; 0.570 for total costs). There was, however, a slight cost advantage to planned CD in women with a prior cesarean. Conclusions : In women with class III obesity, IOL is less costly than planned CD if the probability of vaginal delivery after IOL in an individual patient is greater than 57%.